Oral rabies vaccination of dogs-Experiences from a field trial in Namibia. - Conrad Martin Freuling; Frank Busch; Adriaan Vos; Steffen Ortmann; Frederic Lohr; Nehemia Hedimbi; Josephat Peter; Herman Adimba Nelson; Kenneth Shoombe; Albertina Shilongo; Brighton Gorejena; Lukas Kaholongo; et al. (Public Library of Science (PLoS), 2022)
Dog-mediated rabies is responsible for tens of thousands of human deaths annually, and in resource-constrained settings, vaccinating dogs to control the disease at source remains challenging. Currently, rabies elimination efforts rely on mass dog vaccination by the parenteral route. To increase the herd immunity, free-roaming and stray dogs need to be specifically addressed in the vaccination campaigns, with oral rabies vaccination (ORV) of dogs being a possible solution. Using a third-generation vaccine and a standardized egg-flavoured bait, bait uptake and vaccination was assessed under field conditions in Namibia. During this trial, both veterinary staff as well as dog owners expressed their appreciation to this approach of vaccination. Of 1,115 dogs offered a bait, 90% (n = 1,006, 95%CI:91-94) consumed the bait and 72.9% (n = 813, 95%CI:70.2-75.4) of dogs were assessed as being vaccinated by direct observation, while for 11.7% (n = 130, 95%CI:9.9-17.7) the status was recorded as "unkown" and 15.4% (n = 172, 95%CI: 13.4-17.7) were considered as being not vaccinated. Smaller dogs and dogs offered a bait with multiple other dogs had significantly higher vaccination rates, while other factors, e.g. sex, confinement status and time had no influence. The favorable results of this first large-scale field trial further support the strategic integration of ORV into dog rabies control programmes. Given the acceptance of the egg-flavored bait under various settings worldwide, ORV of dogs could become a game-changer in countries, where control strategies using parenteral vaccination alone failed to reach sufficient vaccination coverage in the dog population.